Chloroform‐sensing properties of plasmonic nanostructures using poly(methyl methacrylate) transduction layer. (1st February 2013) - Ma, Wenying; Luo, Ji; Ling, Weiwei; Wang, Weimin
Abstract : The design and development of a sensitive, fast and selective chloroform vapour sensor based on a poly(methyl methacrylate) (PMMA) transduction layer and a plasmonic nanostructures transducer is presented. The PMMA layer swelled when it was in exposure to the vapours, which would in turn bring in an extinction efficiency change in the localised surface plasmon resonance (LSPR) spectrum for triangular silver nanoprisms. The LSPR spectral response to chloroform and other vapours was measured by a UV–vis spectrometer in real time. Experiment results showed that the PMMA–LSPR sensor indicated a sensitivity of 4.76 × 10 −5 ppm −1 and a detection limit of 21 ppm. A fast, stable and reversible response was observed during positive and negative test cycles upon variations of the environment in the gas cell between clean air and saturated chloroform contained air. The PMMA–LSPR sensor also showed good selectivity of chloroform when it was exposed to vapours with different functional groups. It has been demonstrated that plasmonic nanostructures coated with PMMA transduction films can be applied to chloroform sensing and vapour classifying applications.